Systemic treatment with a novel basic fibroblast growth factor mimic small-molecule compound boosts functional recovery after spinal cord injury. - Shiro Imagama; Ryoko Ogino; Shinya Ueno; Norihito Murayama; Naohiro Takemoto; Yoshiari Shimmyo; Taisuke Kadoshima; Shigeki Tamura; Mariko Kuroda; Yukihiro Matsuyama; Kenji Kadomatsu; Yasuhiro Morita; et al. (PLoS ONE, 2020)
Neurotrophic factors have been regarded having promising potentials for neuronal protection and regeneration, and thus promoting beneficial effects of kinesiological functions. They can be suspected to play important roles in cell/tissue grafting for various neural diseases. The clinical applications of such trophic factors to the central nervous system (CNS), however, have caused problematic side effects on account of the distinctive bioactive properties. In the course of developing synthetic compounds reflecting beneficial properties of basic fibroblast growth factor (bFGF), we conducted screening candidates that stimulate to trigger the intracellular tyrosine phosphorylation of FGF receptor and lead to the subsequent intracellular signaling in neurons. A small synthetic molecule SUN13837 was characterized by mimicking the beneficial properties of bFGF, which have been known as its specific activities when applied to CNS. What is more remarkable is that SUN13837 is eliminated the bioactivity to induce cell proliferation of non-neuronal somatic cells. On the bases of studies of pharmacology, behavior, physiology and histology, the present study reports that SUN13837 is characterized as a promising synthetic compound for treatment of devastating damages onto the rat spinal cord.